Hacia una des-categorización de la ‘identidad hispanoamericana’: estrategias queer en Roberto Bolaño y Pedro Lemebel (Altre Modernità, 2017)
The presence of queer motifs in contemporary Latin American literature is getting more and more relevant nowadays, generating a rich and complex corpus of texts where the thematic obsession with the opaque, incongruous, mischievous body overtly exceeds the LGBT borders and becomes a strategy of experimenting new politics and poetics of representing Latin American collective identity. This essay aims at giving a new theoretically hybrid frame of reading to some of the most emblematic texts of the contemporary canon, one where the postcolonial discourse mixes with queer studies. A classic urban chronicle about transvestism by Pedro Lemebel and the novel Woes of the true Policeman by Roberto Bolaño will be considered as case studies: both the faux detective story of a Chilean exiled investigating on his own sexual ambiguity and the magic-realistic performance of a indio imitator of the pop singer Madonna seems to allude to a sort of subversive continuation of the postcolonial assessment of the New World, in which notions of “obliqueness”, “unaccountability” and, crucially, “vulnerability” sound ambiguously as a critical response and as an ingenious actualization of traditionally fostered cultural constructs such as “mestizaje” and hybridization.